Cross‐sectional relation of long‐term glucocorticoids in hair with anthropometric measurements and their possible determinants: A systematic review and meta‐analysis. (22nd November 2021) - van der Valk, Eline; Abawi, Ozair; Mohseni, Mostafa; Abdelmoumen, Amir; Wester, Vincent; van der Voorn, Bibian; Iyer, Anand; van den Akker, Erica; Hoeks, Sanne; van den Berg, Sjoerd; de Rijke, Yolanda; Stalder, Tobias; et al.
Summary: Background: Long‐term glucocorticoids (HairGC) measured in scalp hair have been associated with body mass index (BMI), waist circumference (WC), and waist‐hip‐ratio (WHR) in several cross‐sectional studies. We aimed to investigate the magnitude, strength, and clinical relevance of these relations across all ages. Methods: We performed a systematic review and meta‐analysis (PROSPERO registration CRD42020205187) searching for articles relating HairGC to measures of obesity. Main outcomes were bivariate correlation coefficients and unadjusted simple linear regression coefficients relating hair cortisol (HairF) and hair cortisone (HairE) to BMI, WC, and WHR. Results: We included k  = 146 cohorts ( n  = 34, 342 individuals). HairGC were positively related to all anthropometric measurements. The strongest correlation and largest effect size were seen for HairE‐WC: pooled correlation 0.18 (95%CI 0.11–0.24; k  = 7; n  = 3, 158; I 2  = 45.7%) and pooled regression coefficient 11.0 cm increase in WC per point increase in 10‐log‐transformed HairE (pg/mg) on liquid‐chromatography‐(tandem) mass spectrometry (LC–MS) (95%CI 10.1–11.9 cm; k  = 6; n  = 3, 102). Pooled correlation for HairF‐BMI was 0.10 (95%CI 0.08–0.13; k  = 122; n  = 26, 527; I 2  = 51.2%) and pooled regression coefficient 0.049 kg/m 2 per point increase in 10‐log‐transformed HairF (pg/mg) on LC–MS (95%CI 0.045–0.054 kg/m 2 ; k  = 26; n  = 11, 635). Discussion: There is a consistent positive association between HairGC and BMI, WC, and WHR, most prominently and clinically relevant for HairE‐WC. These findings overall suggest an altered setpoint of the hypothalamic–pituitary–adrenal axis with increasing central adiposity.